How Early Life Stress Impact Maternal Care: A Systematic Review of Rodent Studies - Orso, Rodrigo; Creutzberg, Kerstin Camile; Wearick-Silva, Luis Eduardo; Wendt Viola, Thiago; Tractenberg, Saulo Gantes; Benetti, Fernando; Grassi-Oliveira, Rodrigo (Frontiers in Behavioral Neuroscience, 2019)
Background: Maternal care refers to the behavior performed by the dam to nourish and protect her litter during its early development. Frequent and high-quality performance of such maternal behaviors is critical for the neurodevelopment of the pups. Maternal exposure to stress during early development can impair maternal care and amplify the deleterious effects of poor maternal caregiving and neglect. As such, a thorough understanding of the effects caused by several models of early life stress on maternal care may yield more insights into the relationship between stress and maternal behavior. Methods: A systematic review was performed to identify and address the effects of early life stress on maternal behavior. The search was conducted using three online databases: PUBMED, Embase and Web of Science. To provide clear evidence of the impact of stress on maternal care, in every study, the stress group was always compared to a control group. Outcomes were categorized into eight different behaviors: (1) licking/grooming; (2) arched-back nursing; (3) blanket-nursing/passive nursing; (4) nest building; (5) contact with pups; (6) harmful/adverse caregiving; (7) no contact; (8) nest exits. Additionally, the methodological quality of the studies was evaluated. Results: A total of 12 different early life stress protocols were identified from the 56 studies included in this systematic review. Our data demonstrate that different stress models can promote specific maternal patterns of behavior. Regarding the maternal separation protocol, we observed an overall increase in nursing and licking/grooming behaviors, which are essential for pup development. An increase in the number of nest exits, which represents a fragmentation of maternal care, was observed in the limited bedding protocol, but the total amount of maternal care appears to remain similar between groups. Conclusions: Each stress protocol has unique characteristics that increase the difficulty of rendering comparisons of maternal behavior. The increase in maternal care observed in the maternal separation protocol may be an attempt to overcompensate for the time off-nest. Fragmented maternal care is a key component of the limited bedding protocol. Moreover, the methodological approaches to evaluate maternal behavior, such as time, duration and behavior type should be more homogeneous across studies.